Ensino de leitura: a interpretação de texto através do subtipo do gênero quadrinho, a tira - Silva, Paulo Sergio Melo da (2015)
The purpose of this research is to first analyze the functions of verbal and non-verbal resources of the comic genre, and more specifically subtype, the strip in relation to reading comprehension and place the reading from the reading strategies in terms of Solé (1998) so that students can explore the linguistic resources that gender presents. It is a documentary research of qualitative and descriptive. During the Portuguese classes, which explored the comic genre which in turn covers the cartoon, the comic strip, the cartoon and comics students had great difficulty in interpreting them. From the difficulties presented by the students, came our interest in exploring better theme in order to overcome the difficulties presented, as well as explore more appropriately what the genre offers as a producer of text directions. The corpus consists of a draft drawn up activities with reference to the Common Curriculum Base (BCC - PE) for the Pernambuco School of Public Networks (2008), applied with 8th graders of elementary school II (2EF), a public school in Olinda-PE. The composite activities of ten (10) exercises involving the comic genre were applied by research professor with the students of the above mentioned class. Such activities were applied so that the first was compared to the past to check the advance in the development of students about this genre. Our results indicate that students are gradually advancing their knowledge comic genre. During this research we realized that the teacher wishing to explore the comic genre, in its Portuguese language classes, you need to know it well, about the risk of failing in this attempt, since it is the teacher's task in his class interpret it from your verbal and non-verbal wealth in this genre. However, based on what we indicate this search, this is not an easy task, the teacher needs to be prepared.